2018
DOI: 10.1016/j.ydbio.2018.03.023
|View full text |Cite
|
Sign up to set email alerts
|

The role of ADHD associated genes in neurodevelopment

Abstract: Attention deficit hyperactivity disorder (ADHD) is a highly heritable neurodevelopmental disorder of childhood. It is primarily characterised by high levels of activity, inattention, and impulsivity, and has strong negative impacts on academic functioning. Children with ADHD show a reduction in volume, and hypoactivity, in a range of brain regions. The underlying mechanisms behind these phenotypes are unknown, however, variants in several genes with known roles in neurodevelopment are associated with ADHD. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
44
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 221 publications
4
44
0
6
Order By: Relevance
“…The hub regions shared by 3 pairs of disorders also overlapped with a handful of interesting candidate genes. SORCS3 (Figure 5B) is highly expressed in the CA1 region of the hippocampus, and is involved in synaptic depression and spatial learning ability 56,57 . It is also known to play an important role in protein networks associated with PICK1, NGF, and PDGF-BB 58,59 which have been implicated in ADHD, ASD, MDD, and SCZ [60][61][62][63] .…”
Section: Discussionmentioning
confidence: 99%
“…The hub regions shared by 3 pairs of disorders also overlapped with a handful of interesting candidate genes. SORCS3 (Figure 5B) is highly expressed in the CA1 region of the hippocampus, and is involved in synaptic depression and spatial learning ability 56,57 . It is also known to play an important role in protein networks associated with PICK1, NGF, and PDGF-BB 58,59 which have been implicated in ADHD, ASD, MDD, and SCZ [60][61][62][63] .…”
Section: Discussionmentioning
confidence: 99%
“…Observations in patients consistently reveal volume reduction in many brain regions, in particular those involved in attention, including the parietal and temporal lobes, the prefrontal and cingulate cortices (for a summary of the regions affected see Dark et al. ). Volume reduction has also been observed in the thalamus, specifically the pulvinar complex (Ivanov et al.…”
Section: Association With Neurodevelopmental Disordersmentioning
confidence: 99%
“…Although the aetiology of the disorder is still unknown, studies have demonstrated the contribution of environmental and genetic factors (for review Dark et al. ). Observations in patients consistently reveal volume reduction in many brain regions, in particular those involved in attention, including the parietal and temporal lobes, the prefrontal and cingulate cortices (for a summary of the regions affected see Dark et al.…”
Section: Association With Neurodevelopmental Disordersmentioning
confidence: 99%
“…Previous work done by Zimmerman et al [ 31 ] showed a 16% decrease in excitatory synapses in mice engineered to display reduced Cfl1 in the striatum, and the High-Active mice displayed reduced Cfl1 ( Fig 2B ). Human ADHD has been associated with genetic variants in synapse-related genes [ 54 ] including synaptophysin [ 55 ]. The genetic association between Lphn3 and ADHD in human populations has been suggested to result from the allele’s effects on synapse stabilization.…”
Section: Discussionmentioning
confidence: 99%